2009
DOI: 10.1002/cncr.24729
|View full text |Cite
|
Sign up to set email alerts
|

Expression of interleukin 15 in primary adult acute lymphoblastic leukemia

Abstract: BACKGROUND:Interleukin‐15 (IL‐15) has been associated with the growth, survival and biological behavior of leukemic cells and response to therapy. We determined the expression of IL‐15 in lymphoblasts and evaluated its potential impact on the outcome in adult acute lymphoblastic leukemia (ALL).METHODS:Between June 1999 and June 2006, ALL samples were collected from 87 adult patients before initiation of antineoplastic therapy. These patients were enrolled in the German Multicenter Acute Lymphoblastic Leukemia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 25 publications
(32 reference statements)
2
17
1
2
Order By: Relevance
“…For this assessment we need Immunophenotypic and cytogenetic prognostic markers for these patients and these markers also help us to divide cases into high and low risk patients Khan et al, (2008). In our study there were 25 (62.5%) males and 15 (37.5%) females, these results were similar to the result of Wu et al,(2010), Reichard et al, (2011) andStacy andPatrick (2015) who reported increase percentage of male than female in childhood ALL patients. The majority of patients with ALL were of B-lymphoid origin.…”
Section: Resultssupporting
confidence: 92%
“…For this assessment we need Immunophenotypic and cytogenetic prognostic markers for these patients and these markers also help us to divide cases into high and low risk patients Khan et al, (2008). In our study there were 25 (62.5%) males and 15 (37.5%) females, these results were similar to the result of Wu et al,(2010), Reichard et al, (2011) andStacy andPatrick (2015) who reported increase percentage of male than female in childhood ALL patients. The majority of patients with ALL were of B-lymphoid origin.…”
Section: Resultssupporting
confidence: 92%
“…In addition to local effects on cell proliferation and survival, IL-15 may facilitate extramedullary dissemination of ALL, promoting bulky mediastinal and LN disease 4 and CNS relapse. 3 IL-15 is directly chemotactic to T cells 32,33 and NK cells 39 and also indirectly influences leukocyte trafficking.…”
Section: Discussionmentioning
confidence: 99%
“…3 Finally, a clinical study looking at IL-15 mRNA in adult ALL showed that higher IL-15 expression was associated with mediastinal and lymph node (LN) infiltration but not hepatosplenomegaly (rates of CNS involvement were not reported). 4 Importantly, some IL-15 SNPs correlate with increased promoter activity when tested in reporter constructs, 5 suggesting a possible direct link to pathogenesis. However, the mechanisms underlying any biological advantage for high IL-15 expression in ALL are currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…These facts suggest that IL-15 may act as a cancer development stimulator in leukemia and lymphomas originating from B cell, T cell and NK cell. Observations such as activated of expression of IL-15 and IL-15R alfa by viral Tax protein in HTLV 1 associated T cell leukemia/lymphoma as well as association of IL-15 expression with mediastinal lymphadenopathy in acute lymphoblastic leukemia (ALL) and poor prognosis and inferior 5 year survival in B cell type ALL and higher risk of CNS relapse in pediatric ALL further supports that IL-15 may act as a cancer development cytokine in hematological malignancies originating from lymphoid cell lines [146,147]. However, observations in solid tumor and cancer cell lines did not show any direct effect of IL-15.…”
Section: Other Interleukinsmentioning
confidence: 80%